The Influence of Cadet-Based Regulations on the Discipline of Taruna Sakti Pekanbaru Middle School Students - Novrizki Khairul Ikhsan; Jumili Arianto; Indra Primahardani (CV. Rayyan Dwi Bharata, 2024)
This research is motivated by problems that often arise in the school environment, for example the lack of discipline among students to follow existing school regulations. Student discipline is often a problem in schools, especially in secondary schools, where students grow up and begin to learn about their identities through imitation, because low discipline can lead to negative student behavior, negative student behavior due to poor self-discipline triggers various violations in school. The purpose of this research is to find out whether there is an influence from the implementation of cadet-based regulations on the discipline of Taruna Sakti Pekanbaru Middle School students. This type of research uses an associative quantitative approach, with data collection techniques using questionnaires, documentation, interviews and literature studies. After considering the data and discussion, it was found that the F test produced F_tab = 4.11 and F_hit = 35.887sq. Since F_hit is greater than F_tab, we can conclude that Ho is rejected and Ha is accepted. Based on this statement, the research hypothesis is accepted. In addition, the influence of cadet-based regulations on student discipline is at a moderate level. Based on the results of these calculations, it can be explained that the relationship value (R) is 0.712. From this output, we get a coefficient of determination (R Square) of 0.506, which means the independent variable (Student Based Regulations) to the dependent variable (Student Discipline) is 50.6%. Based on the results and discussion in this research, it can be concluded that Cadet-Based Regulations have a positive influence on Student Discipline at Taruna Sakti Pekanbaru Middle School.